The Influence of Social Media on Students' Social Interactions - Yanti, Dawi; Ria Kamilah Agustina (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2025)
The widespread use of social media has transformed the way students interact with each other, both online and offline. This study explores the influence of social media on students' social interactions, focusing on its impact on their communication patterns, relationships, and social skills. A mixed-methods approach was employed, combining survey data from 200 students from two universities in Indonesia with in-depth interviews from a subset of participants. The results show that social media has both positive and negative effects on students' social interactions. On the one hand, social media enables students to connect with peers globally, access information, and participate in online discussions. On the other hand, excessive social media use can lead to social isolation, decreased face-to-face communication, and reduced empathy. The study highlights the need for educators and parents to be aware of the potential risks and benefits of social media and to promote healthy social media habits among students. Keywords: social media, social interaction, students, communication, relationships, social skills